Analysis of cone crusher performance with changes in material properties and operating conditions using DEM. (January 2017) - Cleary, P.W.; Sinnott, M.D.; Morrison, R.D.; Cummins, S.; Delaney, G.W.
Highlights: DEM is used to understand breakage and operating performance of a cone crusher. The breakage model uses a replacement strategy and progeny size data from a DWT. There is strong variation in the breakage behaviour with height in the crusher. Larger particles jam in the compression zone prior to breakage and obstruct the flow. Trends in performance with material properties and operating parameters are found. Abstract: Discrete Element Method (DEM) simulation with non-round particles and including breakage has been used to understand the breakage behaviour and operating performance of an industrial scale cone crusher using a representative ore. The breakage model uses a replacement strategy and impact energy specific progeny size data from a Drop Weight Test (DWT). There is a strong variation in the breakage behaviour with height in the compression region as the differing profiles of the concave and mantle create five different regions with monotonically decreasing width and differing degrees of convergence between the surfaces. These control the rate of motion and the ability to load and break the particles, and determine whether high forces are generated via multi-particle stress chains or as single particle loading directly from the liner surfaces. The larger feed particles jam in the compression zone prior to breakage and cause observable obstruction to the flow of finer material and strong non-uniformity in the flow of product down the lower part of the mantle. Trends in the coarseness of product and changes in steady state throughput are identified with changes in material properties (rock breakage energy and friction coefficient) and crusher operating parameters (Closed Side Setting and crusher rotation rate).